Community perceptions and determinants of obstetric fistula across gender lines - Wagaye Fentahun Chanie; Aster Berhe; Ambaye Dejen Tilahun; Bikis Liyew; Chernet Baye; Tarekegn Asemaw Akalie; Destaye Shiferaw Alemu; Miteku Andualem Limenih (Scientific Reports)
Abstract Obstetric fistula is a major maternal health challenge in low-income countries like Ethiopia. Misperceptions about obstetric fistula delay seeking and accessing healthcare. Understanding community attitudes is crucial for prevention, early detection, and support for affected women. A community-based study was conducted from February 1 to April 26, 2024, among 640 women and men to assess attitudes and influencing factors. Participants were selected using a multistage sampling. Multivariable logistic regression analysis was performed, with a p-value < 0.05 considered statistically significant. The study included nearly equal proportions of males (49.1%) and females (50.9%), with a median age of 32 years (IQR: 19–64). Among participants, 47.8% (95%CI: 43.7–51.6) had a favourable attitude towards obstetric fistula. Those under 20 years (AOR: 7.7; 95%CI: 2.3–28.6), aged 20–35 (AOR: 3.9; 95%CI: 1.8–8.5), and aged 36–50 (AOR: 6.36; 95%CI: 3.0–14.1) were more likely to have a favourable attitude compared to those over 50 years. Female gender (AOR: 1.5; 95%CI: 1.1–2.2), primary education (AOR: 1.86; 95%CI: 1.3–2.9), and awareness of obstetric fistula (AOR: 3.04; 95%CI: 2.0–4.6) were significant determinants. The study revealed unfavourable community attitudes towards obstetric fistula, with notable gender and age differences. Enhancing attitudes requires a comprehensive, tailored program involving all relevant stakeholders.